2005
DOI: 10.1007/s00026-004-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

On the Computational Complexity of the Rooted Subtree Prune and Regraft Distance

Abstract: Abstract. The graph-theoretic operation of rooted subtree prune and regraft is increasingly being used as a tool for understanding and modelling reticulation events in evolutionary biology. In this paper, we show that computing the rooted subtree prune and regraft distance between two rooted binary phylogenetic trees on the same label set is NP-hard. This resolves a longstanding open problem. Furthermore, we show that this distance is fixed parameter tractable when parameterised by the distance between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
366
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 228 publications
(366 citation statements)
references
References 15 publications
0
366
0
Order By: Relevance
“…Roughly, each measure corresponds to the size of the appropriately defined maximum agreement forest. For a more thorough treatment, see [5,18,26].…”
Section: Hybridization Network and Agreement Forestsmentioning
confidence: 99%
See 4 more Smart Citations
“…Roughly, each measure corresponds to the size of the appropriately defined maximum agreement forest. For a more thorough treatment, see [5,18,26].…”
Section: Hybridization Network and Agreement Forestsmentioning
confidence: 99%
“…When working with rooted trees, we refer to this distance as rooted SPR or rSPR. Bordewich and Semple [5] showed that the rSPR distance of two trees is the same as the size of an appropriately defined maximum agreement forest for rooted trees of the two trees. This number is related to another measure between trees that we next define.…”
Section: Subtree Prune and Regraft (Spr)mentioning
confidence: 99%
See 3 more Smart Citations